2021
DOI: 10.1016/j.ultsonch.2021.105554
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity ultrasound improves the physical stability of myofibrillar protein emulsion at low ionic strength by destroying and suppressing myosin molecular assembly

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 48 publications
2
37
2
Order By: Relevance
“…The phase separation of the emulsion gradually decreased until it disappeared with the incremental ultrasound power indicating superior creaming behaviour via ultrasound treatment. The emulsions possessed the optimal physical stability when the ultrasound power reached 450 W. Our results were similar to the findings that the MP emulsions showed improved physical stability with a 450 W ultrasonic treatment (Liu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The phase separation of the emulsion gradually decreased until it disappeared with the incremental ultrasound power indicating superior creaming behaviour via ultrasound treatment. The emulsions possessed the optimal physical stability when the ultrasound power reached 450 W. Our results were similar to the findings that the MP emulsions showed improved physical stability with a 450 W ultrasonic treatment (Liu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The study found that ultrasonic treatment improved emulsification properties by reducing particle size of pea proteins [61] . Meanwhile, the particle size of proteins affected EAI, the smaller the proteins, the easier the diffusing, and EAI increased [62] . Here, EAI of raw soymilk reduced, the reason might be that strong ultrasonic cavitation made SP denatured and aggregated into larger particles.…”
Section: Resultsmentioning
confidence: 99%
“…Zeta-potential is a direct indicator of the surface charge density of charged particles [62] , which is used to demonstrate the stability of colloidal system and the electrostatic interaction between particles [25] . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the treated emulsion had better emulsion stability and a higher amount of interfacial proteins. Liu et al [18] evaluated the effect of different HIU powers on the stability of myofibrillar protein (MP) emulsions, and found that the MP emulsion stability was significantly improved at 450 W.…”
Section: Introductionmentioning
confidence: 99%